Discourses on the publick revenues and on the trade of England : in two parts... By the author of the "Essay on ways and means". Part I. To which is added a Discourse upon improving the revenue of the State of Athens, written originally in Greck, by Xenophon, and now made English from the original... by another hand. [-Part II. Tho which is added the late Essay on the East-India trade, by the same hand.] - Davenant, Charles (1656-1714)
Par Charles Davenant, auteur des "Ways and Means. - A la fin du vol. 1, les "Revenus d'Athènes" de Xénophon traduits en anglais ont une pagination et une page de titre propres et sont éd. par James Knapton à Londres en 1697. Trad. par Walter Moyle d'après BN Cat. gén. citant Halkett et Laing. - A la fin du vol. 2 : "Essay on the East-India trade by the author of the Essay on Ways and Means" par Charles Davenant, a une page de titre et une pagination propres. - Au verso du faux titre, annonce de la publication d'autres ouvrages de Davenant par le libraire James Knapton. - Catalogue des livres du libraire à la fin du vol. 1